Efek Pengobatan Kombinasi Diminazene Aceturate dan Fenazone terhadap Re-Infestasi Theileria sp. pada Sapi Potong di Kelompok Ternak Ngudi Makmur, Kapanewon Sleman, Sleman, Daerah Istimewa Yogyakarta - Datrianto, Dwi Sunu; Yanuartono, Yanuartono; Paryuni, Alsi Dara; Kurniawati, Yeni (Jurnal Sain Veteriner, 2026)
Ectoparasite infestation in cattle is common in Yogyakarta. Data obtained from the Animal Husbandry and Animal Health Service of Sleman Regency explained that of the entire cattle population in Kapanewon Sleman, 80% experienced ectoparasite infestation. This study aims to determine the effectiveness of antiparasitic drugs against Theileria sp. reinfestation, which primarily attacks livestock in Sleman Regency, Special Region of Yogyakarta. The method used in this study is descriptive, comparing all stages of the results. The parameter for antiparasitic treatment is based on laboratory results that show Theileria sp. infestation in cattle. Observation of the development of the disease is carried out by periodically examining blood parasites and ectoparasites. The results of this study indicate that treatment using Diminazene Aceturate and Fenazone is effective against Theileria sp. parasite infestation, this is evidenced by negative results in post-treatment blood tests. Monitoring of disease development is done by conducting a blood test again, the results found that there was a reinfestation of Theileria sp. in livestock, this can occur due to poor cage hygiene management which causes Haemaphisalis sp. and Rhipicephalus sp. infestation to continue to develop in the environment as a vector of Theileria sp.